Sex‐specific effects of the Huntington gene on normal neurodevelopment. Issue 1 (7th November 2016) - Lee, Jessica K.; Ding, Yue; Conrad, Amy L.; Cattaneo, Elena; Epping, Eric; Mathews, Kathy; Gonzalez‐Alegre, Pedro; Cahill, Larry; Magnotta, Vincent; Schlaggar, Bradley L.; Perlmutter, Joel S.; Kim, Regina E.Y.; et al.
Abstract : Huntington disease is a neurodegenerative disorder caused by a gene ( HTT ) with a unique feature of trinucleotide repeats ranging from 10 to 35 in healthy people; when expanded beyond 39 repeats, Huntington disease develops. Animal models demonstrate that HTT is vital to brain development; however, this has not been studied in humans. Moreover, evidence suggests that triplet repeat genes may have been vital in evolution of the human brain. Here we evaluate brain structure using magnetic resonance imaging and brain function using cognitive tests in a sample of school‐aged children ages 6 to 18 years old. DNA samples were processed to quantify the number of CAG repeats within HTT . We find that the number of repeats in HTT, below disease threshold, confers advantageous changes in brain structure and general intelligence (IQ): the higher the number of repeats, the greater the change in brain structure, and the higher the IQ. The pattern of structural brain changes associated with HTT is strikingly different between males and females. HTT may confer an advantage or a disadvantage depending on the repeat length, playing a key role in either the evolution of a superior human brain or development of a uniquely human brain disease. © 2016 Wiley Periodicals, Inc. Abstract : Huntington's Disease is a neurodegenerative disorder caused by a gene with trinucleotide repeats ranging from 10–35 in healthy people, and when expanded beyond 39, causes disease. We evaluated healthy children, showing that the number of repeats in this gene, below disease threshold, confer advantageous changes in a sex‐specific manner.